Nanoestructured bridged silsesquioxanes via sol-gel synthesis - Romeo, Hernan Esteban (2008)
Two types of hybrid materials with different degree of nanoestructuring (a bridged silsesquioxane (BS) and hybrid microspheres (MS)) were obtained from a bridged precursor (P) synthesized by the reaction of glycidoxypropyl(trimethoxysilane) with cyclohexylamine. The polycondensation of P in presence of formic acid produced a hybrid material (BS) exhibiting a short-range order based on elongated organic channels, accommodating the cyclohexyl fragments pending from the organic bridge, bounded by inorganic domains. Also, nanostructured hybrid microspheres (MS) were synthesized from P by employing ultrasound-assisted sol-gel processing. The mild reaction conditions produced the nanostructuring of the silsesquioxane characterized by a fine structure in SAXS spectrum. Inorganic domains were arranged in a twodimensional hexagonal system leading to the formation of cavities in the microspheres which could be employed as host-guest systems in advanced technologies.